Pengembangan Sistem Informasi Pembelian Obat Secara Kredit Pada Apotik Dengan Menggunakan Model View Controller (MVC) - Hidayati, Nur (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Purchasing is one of the important areas within the organization. This is because, in the event of purchasing activities, it can meet the needs of supplies needed in an organization, such as the needs of medicines in pharmacies. If the supply of the drug in the pharmacy is thinning, then a purchase is made. At present, there are still many pharmacies that use conventional systems in managing their data. This caused various problems such as the recording of data still using handwriting, drug searches took a long time, and still used a lot of paper in the data documentation. Thus the running purchasing system becomes less effective and efficient. Therefore, there needs to be a system developed in the purchasing system, with the aim that the new system developed can solve the problem and can assist in the management of the data so that the data generated is more accountable and accountable. In order to achieve this goal, appropriate methods such as the use of the Model View Controller (MVC) are required. This MVC method can demonstrate the needs needed in the development of the system. And the result obtained from the use of this MVC method is that it can separate the application logic process with its user interface.